Agreement Between Communities: Tradition and Practice in Sawai Village, North Seram Sub-District, Central Maluku - Nabila, Syadzwina Hindun; Agustina Balik; Wijaya Natalia Panjaitan (KRTHA BHAYANGKARA, 2025)
This research aims to examine and analyze the Solutions in Conflict Resolution over Agreements made by the Community of Sawai Village, North Seram District, Central Maluku Regency. Agreements are part of the relationships between citizens in their daily lives. The agreements used by the community of Sawai Village, Central Maluku Regency, often rely on verbal agreements and frequently depend on trust and individual reputation within the community, where verbal agreements are considered complete upon the delivery and acceptance of an item. The agreements made are often unwritten and based on social norms and traditions. Sawai Village, as the oldest village in Maluku, is surrounded by natural beauty rich in marine resources and forests, and has a strong social structure, where social norms and customs function as regulators of behavior and interactions among individuals. The use of verbal agreements also has the potential to harm both parties. One of them is the lack of verifiable evidence in case of a dispute. This ambiguity can lead to conflicts between parties, where each individual may have a different interpretation of the contents of the agreement. Without written documentation, the dispute resolution process becomes difficult and often relies on witness testimony, which can vary. The research method used is sociological legal research, which is a combination of doctrinal legal research methods and empirical legal research methods. The results of this research indicate that the spoken agreements made by the community in Sawai Village are a phenomenon that reflects strong social and cultural values, and serve as a practical transaction tool in daily life. Although its validity is recognized by law, the main challenge lies in proving and enforcing it when disputes arise.